Agricultural Issues on the Ballot: A Case Study of the 2009 Ohio Issue 2 Campaign - Hannah Thompson; Emily Rhoades-Buck (Journal of Applied Communications, 2013)
This in-depth case study explored the marketing of the November 2009 ballot initiative that created the Ohio Livestock Care Standards board. Key individuals who were involved in communications campaigns dealing with the ballot initiative were interviewed and media coverage was closely analyzed. The interviews examined questions dealing with the origin of the initiative, the types of media used to promote it, the budget for the media campaign and which types of media were viewed as the most valuable and successful. The information obtained reveals which types of media are most effective in reaching consumers about agricultural issues according to campaign organizers. By examining a successful agricultural communications campaign, insight can be gained about how other groups can best reach the public and persuade them to support legislation benefiting the agricultural industry.
Keywords: ballot initiatives; media campaigns; legislation; case study